ChemInform Abstract: Magnetocaloric Effect in AlFe2B2: Toward Magnetic Refrigerants from Earth‐Abundant Elements. Issue 41 (19th September 2013) - Tan, Xiaoyan; Chai, Ping; Thompson, Corey M.; Shatruk, Michael
Abstract The title compound is synthesized from the elements either by arc‐meltingand subsequent annealing at 1173 K for 7 d or by reaction in a Ga flux (alumina crucible, 1173 K, 7 d).